2022
DOI: 10.1155/2022/6124374
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomes Derived from SW480-Resistant Colon Cancer Cells Are Promote Angiogenesis via BMP-2/Smad5 Signaling Pathway

Abstract: Background. Multidrug resistance is the main cause of tumor recurrence and metastasis. Therefore, it is urgent to explore the mechanism and treatment of drug resistance of tumor cells. We aim to investigate the relationship between drug resistance and angiogenesis in SW480 colon cancer cells and the possible underlying mechanism. Methods. Exosomes were extracted from SW480-sensitive or SW480-resistant colon cancer cells (SW480/oxaliplatin). The CCK-8 assay, migration assay, tube formation assay, qPCR, and West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…Furthermore, pi3k and akt1 , downstream genes of the Notch1/Vegfr2 pathway, exhibited a significant decrease after 30 ng/L BDP exposure. Additionally, smad5 , angptl4 , mmp2 , and mmp14 , responsible for angiogenesis and vascular development, were downregulated in offspring following parental exposure to BDP. The observed gene expression patterns are shown in Figure S6B.…”
Section: Results and Discussionmentioning
confidence: 99%